CXCR1 and SLC11A1 polymorphisms affect susceptibility to cutaneous leishmaniasis in Brazil: a case-control and family-based study - Oliveira Joyce; Menezes Eliane; Miller E Nancy; Jamieson Sarra E; Castellucci Léa; Magalhães Andrea; Guimarães Luiz; Lessa Marcus; de Jesus Amélia; Carvalho Edgar M; Blackwell Jenefer M (BMC, 2010)
Abstract Background L. braziliensis causes cutaneous (CL) and mucosal (ML) leishmaniasis. Wound healing neutrophil (PMN) and macrophage responses made following the bite of the vector sand fly contribute to disease progression in mice. To look at the interplay between PMN and macrophages in disease progression in humans we asked whether polymorphisms at genes that regulate their infiltration or function are associated with different clinical phenotypes. Specifically, CXCR1 (IL8RA) and CXCR2 (IL8RB) are receptors for chemokines that attract PMN to inflammatory sites. They lie 30-260 kb upstream of SLC11A1, a gene known primarily for its role in regulating macrophage activation, resistance to leishmaniasis, and wound healing responses in mice, but also known to be expressed in PMN, macrophages and dendritic cells. Methods Polymorphic variants at CXCR1, CXCR2 and SLC11A1 were analysed using Taqman or ABI fragment separation technologies in cases (60 CL; 60 ML), unrelated controls (n = 120), and multicase families (104 nuclear families; 88 ML, 250 CL cases) from Brazil. Logistic regression analysis, family-based association testing (FBAT) and haplotype analysis (TRANSMIT) were performed. Results Case-control analysis showed association between the common C allele (OR 2.38; 95% CI 1.23-4.57; P = 0.009) of CXCR1_rs2854386 and CL, supported by family-based (FBAT; Z score 2.002; P = 0.045) analysis (104 nuclear families; 88 ML, 250 CL cases). ML associated with the rarer G allele (Z score 1.999; P = 0.046). CL associated with a 3' insertion/deletion polymorphism at SLC11A1 (Z score 2.549; P = 0.011). Conclusions The study supports roles for CXCR1 and SLC11A1 in the outcome of L. braziliensis infection in humans. Slc11a1 does not influence cutaneous lesion development following needle injection of Leishmania in mice, suggesting that its role here might relate to the action of PMN, macrophage and/or dendritic cells in the wound healing response to the sand fly bite. Together with the CXCR1 association, the data are consistent with hypotheses relating to the possible role of PMN in initiation of a lesion following the delivery of parasites via the sand fly bite. Association of ML with the rare derived G allele suggests that PMN also have an important positive role to play in preventing this form of the disease.